Analysis of Challenges and Opportunities for the Development of Economic Globalization in Business Law in Indonesia - Hasiholan Sihaloho; Subhan Zein; Nelson Hasibuan; Mario Alberto Manodohon (PT FORMOSA CENDEKIA GLOBAL, 2023)
Globalization as the rapid growth of interdependence and connections in the world of trade and finance. Globalization is not only limited to the phenomenon of trade and financial flows which are growing increasingly widespread, this is due to other trends driven by communication. What are the challenges and opportunities for the development of economic globalization in business law in Indonesia? 1) Business competition regulations, business law regulates fair business competition and prohibits business practices that harm consumers or competitors. This ensures that the market remains healthy and prevents monopolies from harming the economy. Contracts and contract law. 2) Business law regulates the creation, interpretation, and enforcement of contracts. This provides legal certainty for parties involved in business transactions and allows contractors to rely on contract fulfillment. 3) Banking and financial regulations, regulation and supervision of all financial activities must be carried out with integrity. 4) Protection of Intellectual Property Rights (IPR). Business law protects copyrights, patents, trademarks, and industrial designs that encourage innovation and the creation of new goods and services. This provides incentives to companies and individuals to invest in research and development.